Building a better mouse. - Epstein, Jeffrey H. (Futurist, 1998)
Given the growing technical power of personal computers, it is much easier for today's programmers to provide users with a friendlier interface, says cyberjournalist Steven Johnson. In his new book, Interface Culture, Johnson argues that today's typical mouse-and-icon desktop interface, which is itself a direct response to the problems users encountered with the DOS command-line interface, could be improved. A number of such improvements are briefly discussed.